2008
DOI: 10.2136/vzj2007.0108
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Transport of Microbes in Ten Undisturbed Soils under Effluent Irrigation

Abstract: means, electronic or mechanical, including photocopying, recording, or any information storage and retrieval system, without permission in writing from the publisher. ABBREVIATIONS: BTC, breakthrough curve; cfu, colony-forming unit, a unit indicating the number of bacteria present in a water sample; DSE, dairy-shed effl uent; PV, pore volume. ORIGINAL RESEARCHThe HYDRUS-1D mobile-immobile water model (MIM) was used to evaluate the transport of fecal coliforms, Salmonella bacteriophage, and Br in 10 soils. At a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 46 publications
3
59
2
Order By: Relevance
“…Bacteria can only access a smaller range of larger pores due to size exclusion, whereas the chloride can access a wider range of pore sizes. Some other investigators have also observed an earlier breakthrough of bacteria than chloride in intact soils (Guber et al, 2005;Levy et al, 2007;Pang et al, 2008).…”
Section: Transport Of Bacteria Breakthrough Curvesmentioning
confidence: 82%
See 4 more Smart Citations
“…Bacteria can only access a smaller range of larger pores due to size exclusion, whereas the chloride can access a wider range of pore sizes. Some other investigators have also observed an earlier breakthrough of bacteria than chloride in intact soils (Guber et al, 2005;Levy et al, 2007;Pang et al, 2008).…”
Section: Transport Of Bacteria Breakthrough Curvesmentioning
confidence: 82%
“…Some researchers have recognized straining as a potentially important mechanism for bacteria deposition (e.g. Bradford et al, 2004;Gargiulo et al, 2008;Pang et al, 2008). The calculated values of E show that two-site model provides a better performance than one-site model to predict bacteria retention profile (Table 4).…”
Section: Bacteria Distribution In the Soil Columnmentioning
confidence: 96%
See 3 more Smart Citations